Laparoscopic versus open liver resections for intrahepatic cholangiocarcinoma and gallbladder cancer: the Mayo clinic experience. Issue 3 (March 2023) - Pery, Ron; Gudmundsdottir, Hallbera; Nagorney, David M.; Pencovich, Niv; Smoot, Rory L.; Thiels, Cornelius A.; Truty, Mark J.; Vierkant, Robert A.; Warner, Susanne G.; Kendrick, Michael L.; Cleary, Sean P.
Abstract: Background: Data regarding laparoscopic liver resections(LLRs) for Gallbladder cancer(GBC) and Intrahepatic Cholangiocarcinoma(iCCA) are sparse. This study compared LLRs with open liver resections(OLRs) in a high-volume center. Methods: Data of patients who underwent LLR or OLR for GBC or iCCA at Mayo-Clinic between 01/2016 and 04/2021 were retrospectively compared. Proportional hazards models were used to compare the approach on survival. Results: 32 and 52 patients underwent LLR and OLR during the study period, respectively. 64 and 20 patients had iCCA and GBC, respectively. LLR had lower median blood loss (250 mL vs. 475 mL, p = 0.001) and shorter median length of stay compared to OLR (3.0 days vs. 6.0 days, p = 0.001). LLR and OLR did not differ in post-operative major complication (25% vs. 32.7%, p = 0.62), negative margin (100% vs. 90.4%, p = 0.15) and completeness of lymphadenectomy rates (36.8% vs. 45.5%, p = 0.59). The median number of harvested lymph node was 4.0 and 5.0 for LLR and OLR, respectively (p = 0.347). There were no associations between approach and 3-year overall and disease-free survival between LLR and OLR (49.8% vs. 63.2% and 39.6% vs. 21.5%, p = 0.66 and p = 0.69). Discussion: With appropriate patient selection and when compared to OLRs, LLRs for GBC and iCCA are feasible, safe and offer potential short-term benefits without compromising on oncological resection principals and long-term outcomes. Graphical abstract: Image 1